Patient education for older adults with cancer and their caregivers: Protocol for a scoping review - Lu Lin; Janet Papadakos; Rouhi Fazelzad; Kristen Haase; Shabbir Alibhai; Fay Bennie; Martine Puts (PLoS ONE, 2025)
Treatment decision-making for older adults is complex due to multimorbidity, polypharmacy, and age-related changes such as sensory impairment and cognitive decline. In addition, many older adults have lower health literacy, which impacts their ability to access, understand, and apply health information. Patient education plays a critical role to comprehend a new cancer diagnosis, explore treatment options, and manage care effectively. To be effective, education materials must be specifically tailored to the needs of this population. Despite growing recognition of the importance of geriatric-specific cancer education, no recent review has synthesized the literature on educational interventions or materials developed for this population. This review aims to answer the question: What is known about patient education interventions and materials developed for older adults with cancer and their caregivers and their effectiveness to improve outcomes?. We will follow the Arksey and O’Malley framework, refined by Levac et al., and report according to the PRISMA-ScR checklist. We will search Medline ALL, Embase, Emcare, Cochrane Central, PsycInfo (all via OvidSP), and Scopus (via Elsevier) for studies published from 2000 onward and complete a manual search of the references of included studies. A health sciences librarian conducted the searches. We will include peer-reviewed and relevant grey literature. Stakeholder consultation will be conducted to inform interpretation of findings and identify gaps. Eligible studies will use qualitative or quantitative designs focused on geriatric oncology patient education. Two reviewers will independently screen studies and extract data using Covidence and Excel. Data will be analyzed using descriptive statistics and narrative synthesis. The quality of peer-reviewed studies will be appraised with the Mixed Methods Appraisal Tool (2018) for descriptive purposes only. This scoping review will map existing educational interventions and materials for older adults with cancer, support clinicians in practice, and highlight gaps to inform future research and development.